2016
DOI: 10.5433/1679-0359.2016v37n4p1811
|View full text |Cite
|
Sign up to set email alerts
|

Base temperature as a function of genotype: a foundation for modeling phenology of temperate fruit species

Abstract: To complete each phase of the growing season, plants must accumulate thermal time at lower base temperature (Tb). Little information exists on Tb variation between either fruit species or cultivars of the same species. We therefore aimed to determine the lower base temperature for contrasting genotypes in precocity of peach, plum, grape, pear, and kiwi. Twigs 25-35 cm long for the following cultivars: peach, Tropic Beauty (TB) and Eragil (ER); plum, Gulf Blaze (GB) and Letícia (LE); grape, Chardonnay (CH) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…This study confirms the findings of other researchers (Baker et al, 1986;Gallagher 1979;Sayed 1995;Stinner et al 1974) that changes in the phenological stages are the best markers for the fruit species for forecasting their behaviour with the increasing outside air temperature; however, there are differences in the base temperature values among the species, cultivars, and phenological states (Borges et al 2017;Kerr et al 1981;Rafael and Biasi 2016;Ribeiro et al 2009;Salinger and Kenny 1995;Souza et al 2011;Taghavi et al 2017). The strongest correlation of the observed phenological data was always on the same threshold values in both countries; in the case of leafing, the best correlation was at Tb5.5.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…This study confirms the findings of other researchers (Baker et al, 1986;Gallagher 1979;Sayed 1995;Stinner et al 1974) that changes in the phenological stages are the best markers for the fruit species for forecasting their behaviour with the increasing outside air temperature; however, there are differences in the base temperature values among the species, cultivars, and phenological states (Borges et al 2017;Kerr et al 1981;Rafael and Biasi 2016;Ribeiro et al 2009;Salinger and Kenny 1995;Souza et al 2011;Taghavi et al 2017). The strongest correlation of the observed phenological data was always on the same threshold values in both countries; in the case of leafing, the best correlation was at Tb5.5.…”
Section: Resultssupporting
confidence: 90%
“…The strongest correlation of the observed phenological data was always on the same threshold values in both countries; in the case of leafing, the best correlation was at Tb5.5. This value is higher than the amount predicted for grape cultivars 'Chardonnay' (Tb = 2.1 °C) and 'Cabernet Sauvignon' (Tb = 4.3 °C), kiwifruit 'Golden King' (Tb = 4.3 °C), plum 'Gulf Blaze' (Tb = 2.2 °C), pear 'Smith' (Tb = 4.4 °C), peach 'Tropic beauty' (Tb = 2 °C) (Rafael and Biasi 2016), and hazelnut cultivars (Tb = 2 °C) (Taghavi et al 2017). The kiwifruit cultivar 'Hayward' (Tb = 10 °C, Kerr et al 1981;Salinger and Kenny 1995;Tb = 8.2 °C, Rafael and Biasi 2016), the pear cultivar 'Packham's' (Tb = 8.2 °C, Rafael and Biasi 2016), the plum cultivar 'Letícia' (Tb = 6.2 °C, Rafael and Biasi 2016), the grape cultivars 'BRS Victo-K Souza et al 2011), were found to require higher base temperature values than the Persian walnut cultivars involved in our study.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…The determination of the base temperature is an expensive process, since each species has a base temperature which may very in accordance with the plant genotype and the growing season (Anzanello & Biasi, 2016). In temperate species, leaf growth and expansion start before reaching the temperature of 10°C and, in subtropical species, growth does not occur below 12 to 15°C (Hatfield & Prueger, 2015).…”
Section: Introductionmentioning
confidence: 99%